Uptake and transport of antibiotic kasugamycin in castor bean (Ricinus communis L.) seedlings - Zhang, Hongzhen; Zhang, Chenghua; Xiang, Xiaolong; Zhang, Qilun; Zhao, Wei; Wei, Guoyu; Hu, Anlong (Frontiers in Microbiology, 2022)
Kasugamycin (KSM), an aminoglycoside antibiotic, has been widely used for the management of plant diseases, especially for the control of rice blast in Asia. However, its uptake mechanism and transport in plants are still obscure. The castor bean (Ricinus communis L.) seeding, a model plant for phloem transport, was used to study the mechanism of uptake and transport of KSM. Results showed that cotyledon-applied KSM could transport into the phloem and distributed in root and shoot of plant. The temperature, concentration, and pH had significant effects on the uptake of KSM, indicating that the uptake of KSM was mediated by an active carrier system. Compared with the control, competitive inhibitors of sugar transporters D-glucose, D-chiro-inositol, and phloridzin inhibited 71.03%, 67.95%, and 61.73% uptake of KSM, respectively. Energy inhibitor dinitrophenol (DNP) and carbonyl cyanide chlorophenylhydrazone (CCCP) also affected the uptake of KSM, and the inhibition rates were 34.23% and 48.06%. All the results showed that the uptake of KSM was mediated by a sugar transporter, and it could transport from shoot to root in plants via the phloem. The study preliminary elucidated the plant–microbe interactions in the context of the transport of microbial secondary metabolites in plants. It has certain significance for scientific application of antibiotics and biological control of plant diseases and provides theoretical basis for the development of bidirectional transport pesticides.